2021
DOI: 10.1002/pon.5652
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing the worries of AML patients: Quantifying patient experience using best–worst scaling

Abstract: Context Although patients with acute myeloid leukemia (AML) experience significant toxicities and poor outcomes, few studies have quantified patients' experience. Methods A community‐centered approach was used to develop an AML‐specific best–worst scaling (BWS) instrument involving 13 items in four domains (psychological, physical, decision‐making, and treatment delivery) to quantify patient worry. A survey of patients and caregivers was conducted using the instrument. Data were analyzed using conditional logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Despite physicians reporting that they discussed various treatment options with their patients, most patients in this study did not articulate or had limited understanding about the difference between IC, NIC and BSC. Patients noted the overwhelming shock upon diagnosis [39][40][41], which can make it difficult to process complex information about treatment options [5,41] and to feel involved in treatment decisionmaking [42]. Several patients also described inflated concerns regarding the treatment side effects based on their experiences with family/ friends on other chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite physicians reporting that they discussed various treatment options with their patients, most patients in this study did not articulate or had limited understanding about the difference between IC, NIC and BSC. Patients noted the overwhelming shock upon diagnosis [39][40][41], which can make it difficult to process complex information about treatment options [5,41] and to feel involved in treatment decisionmaking [42]. Several patients also described inflated concerns regarding the treatment side effects based on their experiences with family/ friends on other chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Novel stated preference methods including best-worst scaling (BWS) instruments and discrete choice experiments (DCEs) have recently been developed that can accurately quantify patient preferences [ 17 , 18 ]. BWS instruments have been used to prioritize the values of stakeholders [ 19 ]. Object case BWS instruments (henceforth simply referred to as BWS instruments) are thought to have less cognitive burden on respondents compared with other preference elicitation instruments [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…DCEs require participants to make choices between pairs of hypothetical treatments with different outcomes and have been particularly useful at rigorously quantifying the trade-off preferences of patients for treatments and informing patient-focused drug development [ 7 ]. Through a multistage process involving stakeholder engagement with patients, caregivers, and the FDA, we developed a BWS instrument and a DCE for patients with acute myeloid leukemia (AML) [ 19 , 21 - 23 ]. Using the BWS, we elicited the treatment preferences of 832 patients with AML and demonstrated that patients had the strongest concerns about outcomes in psychosocial and physical domains [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations